Predicting Mother Abuse Based on Spouse\'s Emotional Blackmail and Self-Esteem - Zabihollah Abbaspour; Amir Mohammad Tavakhosh (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām)
Introduction:  Domestic violence, including child, parent, and spousal abuse, is a growing global issue, particularly affecting teenage mothers due to its detrimental effects on the family system. The purpose of this study was to investigate the predictors of mother abuse, focusing on the emotional blackmail of the spouse and self-esteem among first secondary school boys and girls. Materials & Methods: This study employed a correlational research method. The statistical population included all mothers with male and female first secondary school students in the academic year 1401-1402 in Khorramabad city (Iran). A total of 271 participants were selected using the cluster sampling method and consented to participate in the research. The study utilized the Parent Abuse Scale, the Emotional Blackmail Scale, and Eysenck's Self-Esteem Inventory. Data analysis was conducted using SPSS V.22, employing Pearson correlation, simultaneous regression, and stepwise regression techniques at p less than 0.05. Results: The study found a negative correlation between self-esteem and mother abuse, regardless of whether the mother had a son or daughter. Emotional blackmail positively correlated with mother abuse among girls, but not boys. Enter regression analysis showed that emotional blackmail and self-esteem accounted for 21% of parental abuse in boys and 37% in girls. Stepwise regression analysis showed that self-esteem was a significant predictor of mother abuse in girls. Conclusion: The study indicates that family system interactions significantly contribute to parent abuse, with emotional blackmail and self-esteem being key predictors of mother abuse, emphasizing the need to address these factors within the family context.